Paulo Freire’s contributions to EJA in Brazil - Alves, Heryson Raisthen Viana (2021)
Considering Paulo Freire’s influence inBrazil’s educational scenario, our goal is to reflect on the trajectory of Educação de Jovens e Adultos (EJA)/ Youth and Adult Education (YAE), highlighting Freire’s contributions. Based on a review of the main moments of Youth and Adult Education in Brazil, we reflect on its importance in the education of Young people and adults. The discussions are based on dialogues with authors such as Mura (1999) and Freire (2003), references for the modality in Brazil and in the world. The work reaches importante discussions and addresseskey issues in the field of youth and adult education, which is essential to reflection and contact with the área still in the formative process.